Application of Pectin Coating in the Production of Vitamin Fortified Rice - Lalita Chatiyanont; Phaisan Wuttijumnong (Agriculture and Natural Resources, 2007)
The quantity of vitamins in rice grain is decreased by milling, washing and cooking process. Therefore, the production of vitamin fortified rice using edible coating was investigated. Three types of low methoxyl pectin (36% degree of methoxyl, 31% degree of methoxyl with 21% degree of amidation and 28% degree of methoxyl with 18% degree of amidation) and control (no pectin coating) were studied. The results showed that L* a* b* values and moisture contents of rice premix were not significantly different (p > 0.05). Their values were 71.67-73.00, 13.07-14.32, 78.97-80.92 and 8.01-8.93%, respectively. Rice premix coated with pectin at 36% degree of methoxyl showed the lowest loss of thiamine, riboflavin and niacin during washing. However, pectin coating could not prevent the significant loss of thiamine and riboflavin during cooking in excess water (p > 0.05). The suitable ratio of rice premix to milled rice was 1:70. The cooked vitamin fortified rice at this ratio had 0.17 mg/100 g of thiamine and 27.89 mg/100 g of niacin content. The results of consumer acceptance test using Central Location Test (CLT) and Home Use Test (HUT) were similar. It was found that vitamin fortified rice was accepted by consumers at 95% (CLT) and 98% (HUT), respectively.